2017
DOI: 10.1371/journal.pcbi.1005314
|View full text |Cite
|
Sign up to set email alerts
|

Is the Conformational Ensemble of Alzheimer’s Aβ10-40 Peptide Force Field Dependent?

Abstract: By applying REMD simulations we have performed comparative analysis of the conformational ensembles of amino-truncated Aβ10-40 peptide produced with five force fields, which combine four protein parameterizations (CHARMM36, CHARMM22*, CHARMM22/cmap, and OPLS-AA) and two water models (standard and modified TIP3P). Aβ10-40 conformations were analyzed by computing secondary structure, backbone fluctuations, tertiary interactions, and radius of gyration. We have also calculated Aβ10-40 3JHNHα-coupling and RDC cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 61 publications
3
27
0
Order By: Relevance
“…All simulations were performed using CHARMM version c41b1 [73] using the CHARMM36 force field, [74] likely to be the most accurate force field for simulation of Aβ. [75] The GBSW implicit membrane solvent model was used, [69] employing a 0.004 kcal mol -1 Å -2 surface tension, 5 Å smoothing length from the membrane core-surface boundary, and 0.6 Å smoothing length at the water-membrane surface boundary, using 24 radial and 38 angular integration points to 20 Å.…”
Section: B Molecular Dynamics Simulationmentioning
confidence: 99%
“…All simulations were performed using CHARMM version c41b1 [73] using the CHARMM36 force field, [74] likely to be the most accurate force field for simulation of Aβ. [75] The GBSW implicit membrane solvent model was used, [69] employing a 0.004 kcal mol -1 Å -2 surface tension, 5 Å smoothing length from the membrane core-surface boundary, and 0.6 Å smoothing length at the water-membrane surface boundary, using 24 radial and 38 angular integration points to 20 Å.…”
Section: B Molecular Dynamics Simulationmentioning
confidence: 99%
“…The shared primary structural feature of Aβ peptides is a central hydrophobic core (CHC) from residues Leu to Ala and a C‐terminal hydrophobic core from Ala to Val with an N‐terminal hydrophilic region from Asp to Lys and central hydrophilic region from Glu to Gly. X‐ray diffraction, solid state NMR, other spectroscopic methods and molecular dynamics (MD) simulations have demonstrated that collapse of CHC and residues 30–36, leads to the formation of a β‐strand‐loop‐β‐strand motif that is important for oligomerization and fibril formation .…”
Section: Introductionmentioning
confidence: 99%
“…The predominance of A fibrils in cerebral cortical tissue does not necessarily correlate with causation of AD or CAA given the finding that A(1-40) is ten times more abundant in cerebrospinal fluid than A(1-42). [14][15][16] The shared primary structural feature of A peptides is a central hydrophobic core (CHC) from residues Leu 17 to Ala 21 and a C-terminal hydrophobic core from Ala 30 to Val 36 with an N-terminal hydrophilic region from Asp 1 to Lys 16 and central hydrophilic region from Glu 22 to Gly 29 . X-ray diffraction, solid state NMR, other spectroscopic methods and molecular dynamics (MD) simulations have demonstrated that collapse of CHC and residues 30-36, leads to the formation of a -strand-loop--strand motif that is important for oligomerization and fibril formation.…”
Section: Introductionmentioning
confidence: 99%
“…29 This behavior may also hold for other forms of A monomers given a recently published MD simulation of A(10-40) using the CHARMM22/cmap and CHARMM36 force fields demonstrated a similar helical motif with excellent agreement with the previously published 3 JHNH  -coupling and RDC constants from the 2LFM solution structure. 30 The lowest order A oligomer that appears to be biologically active is the dimer having been identified in the cerebral tissue of AD patients. 16 Covalently linked synthetic A dimers have also been used to demonstrate rapid oligomerization and fibril formation as well as the development of hyper-phosphorylated tau protein in the cerebral cortex tissue of animal models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation